Specific measurement of tethered running kinetics and its relationship to repeated sprint ability - Sousa, F.; dos Reis, I.; Ribeiro, L.; Martins, L.; Gobatto, C. (Journal of Human Kinetics, 2015)
Repeated sprint ability has been widely studied by researchers, however, analysis of the relationship between most kinetic variables and the effect of fatigue is still an ongoing process. To search for the best biomechanical parameter to evaluate repeated sprint ability, several kinetic variables were measured in a tethered field running test and compared regarding their sensitivity to fatigue and correlation with time trials in a free running condition. Nine male sprint runners (best average times: 100 m = 10.45 ± 0.07 s; 200 m = 21.36 ± 0.17 s; 400 m = 47.35 ± 1.09 s) completed two test sessions on a synthetic track. Each session consisted of six 35 m sprints interspersed by 10 s rest under tethered field running or free running conditions. Force, power, work, an impulse and a rate of force development were all directly measured using the sensors of a new tethered running apparatus, and a one-way ANOVA with Scheffé post-hoc test used to verify differences between sprints (p < 0.05). Pearson product-moment correlation measured the relationship between mechanical variables and free running performance. A total impulse, the rate of force development and maximum force did not show significant differences for most sprints. These three variables presented low to moderate correlations with free running performance (r between 0.01 and -0.35). Maximum and mean power presented the strongest correlations with free running performance (r = -0.71 and -0.76, respectively; p < 0.001), followed by mean force (r = -0.61; p < 0.001) and total work (r = -0.50; p < 0.001). It was concluded that under a severe work-to-rest ratio condition, power variables were better suited to evaluating repeated sprint ability than the other studied variables.